The Earnings Management Effect of IFRS Implementation: Evidence from an Emerging Economy (Acta Universitatis Danubius. Œconomica, 2024)
The issue of earnings management continues to be focus of recent research in accounting due to its implications for capital market. This study assesses the effects of IFRS adoption on earnings management for emerging economy with specific evidence based on comprehensive samples of listed firms on South Africa (SA). Using a sample of 186 listed firms, the procedure supposes a random effect estimation to examine the relationship between earnings management and considered variable, for the “prior-IFRS period (2000 to 2004)” and the “post-IFRS period (2017 to 2022)”. The finding confirms significant negative effect of IFRS-adoption on earnings misreporting, suggesting that IFRS-adoption caused a reduction in earnings manipulations in SA. Moreso, book-to-market values, returns on assets and cash flow from operations significantly explains earnings management practices in SA. Lastly, the outcome is observed to be robust and not sensitive to the methods applied for the test; thus, the evidence can be used to make informed policy decisions. The findings have implication for regulation, policy making, and would boost stakeholder’s interests on the capital market in the economy. We recommend that regulators should ensure regular assessment and quality audits of firms’ reports, as such would enhance the integrity of represented financial information and protect investor’s funds.